Muscle squeezing immediately after coronary reperfusion therapy using postconditioning with lactate-enriched blood. (15th January 2019) - Koyama, Takashi; Munakata, Masahito; Akima, Takashi; Miyamoto, Kazutaka; Kanki, Hideaki; Ishikawa, Shiro
Abstract: Background: We recently reported a new approach for cardioprotection, postconditioning with lactate-enriched blood (PCLeB), and a patient with ST-segment elevation myocardial infarction (STEMI), in whom muscle squeezing of the culprit coronary artery was observed immediately after reperfusion with PCLeB. In this study, we examined the prevalence of muscle squeezing immediately after reperfusion in patients with anterior STEMI treated using PCLeB. Methods and results: PCLeB is a modified postconditioning protocol that comprises intermittent reperfusion and timely coronary injections of lactated Ringer's solution. We treated 30 consecutive patients with anterior STEMI using PCLeB. Among the 30 patients, 4 patients exhibited muscle squeezing of the left anterior descending artery (LAD) immediately after reperfusion. We performed follow-up coronary angiography in 23 patients and found another patient who exhibited muscle squeezing of the LAD. Thus, of 30 patients, 5 were confirmed to have myocardial bridging and 4 exhibited muscle squeezing immediately after reperfusion with PCLeB. No patient died or experienced re-hospitalization for heart failure or recurrent ischemic events at 6 months except for one patient with malignancy. Conclusion: Muscle squeezing immediately after reperfusion therapy is not a rare phenomenon in patients with anterior STEMI treated using PCLeB. Highlights: We recently reported a new approach for cardioprotection, which is postconditioning with lactate-enriched blood (PCLeB). We reported that PCLeB yielded good in-hospital outcomes in patients with ST-segment elevation myocardial infarction (STEMI). We report that muscle squeezing immediately after reperfusion is not a rare phenomenon in patients treated using PCLeB. This result suggests the cardioprotective effects of PCLeB against myocardial stunning or lethal reperfusion injury.